EKSISTENSI ALAT BUKTI DALAM PENGADILAN (STUDI KOMPARATIF MENURUT HUKUM ISLAM DAN HUKUM POSITIF DI INDONESIA) - Azwar, Syahrul (UIN Fatmawati Sukarno Bengkulu, 2018)
The formulation of this research is: First, How is the existence of evidence in the judiciary according to Islamic law? Second What is the existence of evidence in court according to positive law in Indonesia? Third, how do you compare the existence of evidence according to Islamic law and criminal procedural law? This type of research is library research (library research). Data collection uses reading techniques, citing information. This study concludes that: First, according to Islamic law, evidence is anything that has something to do with an act, the evidence can be used as evidence to raise the confidence of the judge over the truth of a criminal act committed by the defendant. Second, the evidence according to positive law is witness testimony, expert testimony, letters, instructions and information from the defendant. Whereas the positive law stipulates that only legal evidence instruments can be used for verification. Third, the position of evidence in Islamic law and Positive Law is a tool to assist the process of verification in criminal proceedings and help the judge to obtain confidence in an alleged act. Islamic law and positive law have several similarities, namely the law governing actions that are related to the soul or members of the body, such as killing, injuring and so on